Computerization Family Counseling: Is it Practical to Building The Welfare and Happiness of Muslim Families in Malaysia - Shamsuddin, Solehah (Universitas Islam Raden Rahmat Malang, 2023)
Family consultation services provided by Malaysian Islamic Religious Offices have emerged as a highly beneficial and practical approach to addressing family difficulties, enhancing well-being, and achieving positive outcomes for Muslim marriages in Malaysia. These services play a vital role in nurturing healthy family relationships and ensuring the overall welfare of Muslim families within the context of religious beliefs. This research seeks to assess the practicality of these services in the current context and propose solutions to enhance overall service delivery. While family consultation holds significant potential, it is essential to address its practical challenge with a focus on its service accessibility. This research attempts to illuminate the usefulness of family consultation services provided by Malaysian Islamic Religious Offices, contributing to the ongoing discourse on its effectiveness for Muslims in the present time. The findings of this study can assist in enhancing the practicality and maximizing the benefits of family consultation services provided by the authority. By gaining insights into the strengths, limitations, and benefits and fostering positive impact, counselors can devise strategies to better meet the needs of Muslim families seeking support. Family consultation services also can continue to contribute to the overall well-being and happiness of Muslim families in Malaysia.